Antibacterial activity of mangrove plant extract of Rhizophora apiculata in inhibiting the growth of various strains of Aeromonas hydrophila - DINI SISWANI MULIA; SUCI DWI RAHAYU; AMAN SUYADI; IKHSAN MUJAHID; ALIM ISNANSETYO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Mulia DS, Rahayu SD, Suyadi A, Mujahid I, Isnansetyo A. 2023. Antibacterial activity of mangrove plant extract of Rhizophora apiculata in inhibiting the growth of various strains of Aeromonas hydrophila. Biodiversitas 24: 4803-4810. Aeromoniasis is a bacterial disease caused by Aeromonas hydrophila. Synthetic antibiotics are often used to treat this disease. However, using antibiotics for too long with excessive doses can cause side effects for the environment, fish, and other aquatic biota. One of the natural ingredients with the potential as an antimicrobial is the mangrove plant Rhizophora apiculata. This study aims to determine the antimicrobial activity of mangrove plant extract R. apiculata in inhibiting the growth of various strains of A. hydrophila. The study used a completely randomized design experimental method with a factorial pattern with 3 factors (plant part, bacterial strain, and extract concentration) with 48 treatments and 3 replications. Methanol (polar) and n-hexane (non-polar) were used as extract solvents. The parts of the plant used are leaves and stems. The bacterial strains used were GPl-04, GB-01, GK-01, GJ-01, GL-01, and GL-02. The concentration of mangrove extract used was 0, 10, 20, and 30%. The inhibition zone diameter measured the antimicrobial activity using a paper disc (Kirby Bauer method). The data analysis used was the non-parametric Kruskall-Wallis test and qualitative descriptive. The results showed that R. apiculata methanol extract's leaves and stems contain bioactive compounds of flavonoids, alkaloids, and tannins, while the n-hexane extract contains terpenoids. Leaves methanol extract R. apiculata exhibited better than stems, namely the inhibition zone diameter of 2.87 mm, at a concentration of 20% against the GJ-01 bacterial strain, while the methanol extract of stem R. apiculata showed the best antimicrobial activity, namely the diameter of the inhibition zone of 2.10 mm, at a concentration of 30% against the bacterial strain GL-02. Leaves n-hexane extract R. apiculata had the best antimicrobial activity at a concentration of 10% against the bacterial strain GL-01, with an inhibition zone diameter of 2 mm. The n-hexane extract of stems R. apiculata showed antimicrobial activity at a 30% concentration of 1.23 mm in the same strain. Mangroves plant R. apiculata have bioactive compounds that can be used as natural bactericides to control A. hydrophila bacterial disease.